Protecting and promoting pastoralism in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2012)
Pastoralism supports tens of millions of people, makes the best use of harsh environments and provides many economic and social benefits. At the Brussels Development Briefing on ‘New Challenges and Opportunities for Pastoralism in ACP Countries’, experts highlighted policies to improve the welfare of livestock herding communities. Providing the focus of this CTA Policy Brief, these policies include: protecting rights to land and water and helping pastoralists secure assets; strengthening pastoral economies and encouraging value-adding and diversification; empowering pastoralists and encouraging dialogue with policy-makers; and investing in essential services for pastoralists.